2020
DOI: 10.3991/ijet.v15i07.13219
|View full text |Cite
|
Sign up to set email alerts
|

Development of Projo Bale Model Based on Android Application in History and Local Wisdom Studies of Malang

Abstract: Lack of research development on history and local wisdom studies of Malang and its integration in learning acitivities is the background of the development of Projo Bale model. Local history is full of relevant local wisdom values to be implanted in learners. The history department as the institution that produce history teachers should teach students with knowledge about local history at least the area of Malang. This Model was compiled in response to the problem. The collaboration between Outdoor Learning an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The attitude of caring for the environment is included in the learning achievement in the affective aspect. Several studies have shown that the use of android-based interactive media will affect student attitudes (Elmunsyah et al, 2019;Sayono et al, 2020). In addition, as a form of learning innovation in the digital era for geography learning, Android-based interactive media can also be integrated with learning models and approaches such as the determination of Android-based interactive media with guided inquiry learning models of Android-based interactive media that were developed integrated with local wisdom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The attitude of caring for the environment is included in the learning achievement in the affective aspect. Several studies have shown that the use of android-based interactive media will affect student attitudes (Elmunsyah et al, 2019;Sayono et al, 2020). In addition, as a form of learning innovation in the digital era for geography learning, Android-based interactive media can also be integrated with learning models and approaches such as the determination of Android-based interactive media with guided inquiry learning models of Android-based interactive media that were developed integrated with local wisdom.…”
Section: Discussionmentioning
confidence: 99%
“…Interactive multimedia makes the learning process more fun, more innovative, interactive, can reduce teaching time, can foster motivation and the quality of student learning, can take place anytime and anywhere, and can improve and focus students' attitudes and attention (Sarac, 2017;Komalasari & Rahmat, 2019;Anggraini & Eddy Sartono, 2019;Amelia et al, 2021). In line with that, the application of interactive multimedia in learning in schools is one of the efforts to solve the problem of the lack of innovation and variations in the use of learning media (Sayono et al, 2020;Xu, 2017). This is because by using the media as a message distributor, it will be able to stimulate the thoughts, feelings, attention and willingness of students so that it can encourage a more interactive and communicative learning process.…”
Section: Introductionmentioning
confidence: 91%
“…According to Saripudin et al (2022), learning resources on local history serve as a foundation for developing students' identities, cultures, and social lives. Additionally, learning local history allows students to conduct, observe and evaluate scientific research at historical places around their community (Sayono et al, 2020). Therefore, it can be inferred that local history is crucial for students to understand since it connects to their familiar region and culture.…”
Section: Local Historymentioning
confidence: 99%
“…Outdoor learning is learning to know the real-life situation [17]. Outdoor learning activities take advantage of the potential of the surrounding environment as a classroom [18]. By engaging in the field, students become active in exploring the site with a comprehensive understanding.…”
Section: Introductionmentioning
confidence: 99%